2019
DOI: 10.1080/00140139.2018.1556816
|View full text |Cite
|
Sign up to set email alerts
|

The impact of external facial features on the construction of facial composites

Abstract: This is a repository copy of The impact of external facial features on the construction of facial composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…What is possible here is that media outlets cropped the image for space, but another possibility is for stylistic reasons (to show the central part of the face); however, provisional research from our laboratory indicates that revealing less than a complete face may not be best for identification. Much better, as our research has shown recently [19], would be to present the face with alternative representations including hat and sunglasses. Clearly, additional research is needed to clarify what should be best practice, and to identify the reason why published images have not faithfully represented the original composite, as constructed by a witness.…”
Section: (B) Public Appeals Involving Non-evofit Compositesmentioning
confidence: 94%
See 1 more Smart Citation
“…What is possible here is that media outlets cropped the image for space, but another possibility is for stylistic reasons (to show the central part of the face); however, provisional research from our laboratory indicates that revealing less than a complete face may not be best for identification. Much better, as our research has shown recently [19], would be to present the face with alternative representations including hat and sunglasses. Clearly, additional research is needed to clarify what should be best practice, and to identify the reason why published images have not faithfully represented the original composite, as constructed by a witness.…”
Section: (B) Public Appeals Involving Non-evofit Compositesmentioning
confidence: 94%
“…These include improvements to the initial interview (to give an 'enhanced' H-CI), EvoFIT system (mechanism for setting facial width, selection by focusing on the eye region, new face and accessory databases) and postproduction (incl. stretched composite and hats-and-sunglasses format) [ [19]. Enhancements were discussed with practitioners, to elicit feedback, and included in (i) training courses for new practitioners and (ii) annual workshops for existing practitioners.…”
Section: (B) Uptake Of Procedural Enhancementsmentioning
confidence: 99%
“…Unfortunately, composites are generally poorly recognised by people who are familiar with the person being portrayed (e.g., Davies & Valentine, ; Frowd, Carson, Ness, McQuiston‐Surrett, et al, ; Frowd, Carson, Ness, Richardson, et al, ; Frowd et al, ; Valentine & Davis, ; Zahradnikova, Duchovicova, & Schreiber, ). Most research on composite construction has consequently focused on identifying the reasons why these systems produce such poor likenesses, in order to improve their effectiveness as an aid for the police (e.g., Brown et al, ; Frowd et al, ; Ness, Hancock, Bowie, Bruce, & Pike, ). Early composite systems, such as Photofit and Identikit, were based on a misconceived, “feature‐based,” model of human face processing (Ellis, Davies, & Shepherd, , ; Frowd et al, ; Laughery & Fowler, ).…”
Section: Introductionmentioning
confidence: 99%